Thickness control of 2D nanosheets assembled from precise side-chain giant molecules. Issue 14 (4th March 2021) - Feng, Fengfeng; Guo, Dong; Shao, Yu; Yan, Xiang; Yue, Kan; Pan, Zhipeng; Li, Xiangqian; Xiao, Dongcheng; Jin, Liang; Zhang, Wen-Bin; Liu, Hao
Abstract : Thickness of self-assembled 2D nanosheets is not necessarily proportional to the contour length (or molecular weight) of the building blocks. Abstract : The performance of 2D nanomaterials hinges on both the chemical compositions and the morphological structures across different length scales. Among all the three dimensions, thickness is the only one that falls into the nanometer scale and, to some extent, determines the intrinsic properties of 2D nanomaterials. In this study, we report the preparation and precise thickness control of 2D nanosheets assembled from a library of monodispersed amphiphilic giant molecules composed of functional polyhedral oligomeric silsesquioxanes (POSSs) as the side groups. Solution self-assembly of such giant molecules resulted in 2D nanosheets with similar structural configurations, where a bilayer of hydrophobic isobutyl POSS (BPOSS) is sandwiched by two monolayers of hydrophilic POSS bearing carboxylic acid groups (APOSS). The thickness of the obtained nanosheets could be tuned through adjusting the chemical compositions of the pendant POSS cages. Intriguingly, we found that the thickness of the 2D nanosheets was not necessarily proportional to the contour length of the giant molecule nor the total number of POSS cages tethered to the main chain. Indeed, the number ratio of BPOSS to APOSS, rather than the exact number, played a deterministic role in the thickness control. To explain the unusual thickness dependence, we built up a structure model with an in-plane orientation of the giant molecules in the nanosheets, from which a formula was further deduced to semi-quantitatively describe the inverse relationship between the overall thickness and the number ratio of BPOSS to APOSS.